LAMP assay and rapid sample preparation method for on‐site detection of flavescence dorée phytoplasma in grapevine. (23rd July 2014) - Kogovšek, P.; Hodgetts, J.; Hall, J.; Prezelj, N.; Nikolić, P.; Mehle, N.; Lenarčič, R.; Rotter, A.; Dickinson, M.; Boonham, N.; Dermastia, M.; Ravnikar, M.
<x xml:space="preserve">Abstract</x> In Europe the most devastating phytoplasma associated with grapevine yellows (GY) diseases is a quarantine pest, flavescence dorée (FDp), from the 16SrV taxonomic group. The on‐site detection of FDp with an affordable device would contribute to faster and more efficient decisions on the control measures for FDp. Therefore, a real‐time isothermal LAMP assay for detection of FDp was validated according to the EPPO standards and MIQE guidelines. The LAMP assay was shown to be specific and extremely sensitive, because it detected FDp in all leaf samples that were determined to be FDp infected using quantitative real‐time PCR. The whole procedure of sample preparation and testing was designed and optimized for on‐site detection and can be completed in one hour. The homogenization procedure of the grapevine samples (leaf vein, flower or berry) was optimized to allow direct testing of crude homogenates with the LAMP assay, without the need for DNA extraction, and was shown to be extremely sensitive.